2016
DOI: 10.1073/pnas.1608576114
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the golgin GM130 causes Golgi disruption, Purkinje neuron loss, and ataxia in mice

Abstract: The Golgi apparatus lies at the heart of the secretory pathway where it is required for secretory trafficking and cargo modification. Disruption of Golgi architecture and function has been widely observed in neurodegenerative disease, but whether Golgi dysfunction is causal with regard to the neurodegenerative process, or is simply a manifestation of neuronal death, remains unclear. Here we report that targeted loss of the golgin GM130 leads to a profound neurological phenotype in mice. Global KO of mouse GM13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
108
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 53 publications
(77 reference statements)
13
108
0
Order By: Relevance
“…For example, cultured neurons from the central nervous system or dorsal root ganglia degenerate while manifesting early cis ‐GA abnormalities upon depletion of proteins involved in synaptic transmission (syntaxin‐1, Munc18‐1, SNAP‐25) (Santos et al , ). Similarly, specific removal of GA‐relevant proteins can precipitate neurodegeneration in mice (Liu et al , ) . Systemic loss of neutral sphingomyelinase (SMPD3) can cause dwarfism with chondrodysplasia due to GA dysfunction that may be secondary to the altered metabolism of ceramide and diacylglycerol (Stoffel et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cultured neurons from the central nervous system or dorsal root ganglia degenerate while manifesting early cis ‐GA abnormalities upon depletion of proteins involved in synaptic transmission (syntaxin‐1, Munc18‐1, SNAP‐25) (Santos et al , ). Similarly, specific removal of GA‐relevant proteins can precipitate neurodegeneration in mice (Liu et al , ) . Systemic loss of neutral sphingomyelinase (SMPD3) can cause dwarfism with chondrodysplasia due to GA dysfunction that may be secondary to the altered metabolism of ceramide and diacylglycerol (Stoffel et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to determine the contributions of Golgi fragmentation to neurodegenerative diseases, a recent study showed that gene deletion of the golgin GM130 in mice causes severe trafficking defects, concomitant with disruption and aberrant positioning of the Golgi, resulting in the death of Purkinje neurons and ataxia [104**]. Likewise, down-regulation of GM130 in zebrafish leads to microcephaly and muscle defects, which were also observed in a human patient with GM130 mutations who developed microcephaly and neuromuscular disorders [105].…”
Section: Golgi Ribbon Fragmentation Under Pathological Conditionsmentioning
confidence: 99%
“…A comparable phenotype is seen in Purkinje neurons of GM130 knockout mice where only terminal branching and arborization but not initial formation of dendrites is affected. Deletion of GM130 coincides with the loss of AKAP450 from the Golgi [104**], suggesting that defective dendrite branching may be partially attributable to the impaired microtubule nucleation from the Golgi. However, since the extensive dendrite branching of Purkinje cells depends on a functional secretory pathway, it is likely that the severe secretory perturbation further aggravates the phenotype [104**].…”
Section: Golgi Ribbon Fragmentation Under Pathological Conditionsmentioning
confidence: 99%
“…1). These smaller membranes lack detectable levels of some standard Golgi markers (Table 1), like Golgi tether GM130 which is required for mature dendritic arborization (Liu et al 2017; Zhou et al 2014). This suggests that both GO and GS are equally important to dendritic function in a spatiotemporally dependent fashion.…”
Section: Golgi Apparatus In Neuronsmentioning
confidence: 99%